REGULATING THE CRIMINAL LIABILITY OF POLITICAL PARTIES REGARDING CORRUPTION OF FINANCIAL ASSISTANCE FOR POLITICAL PARTIES - Assiddiq H.; Madjid A.; Aprilianda N. (Russian Journal of Agricultural and Socio-Economic Sciences)
Political parties are fundamental pillars of democracy and serve as vehicles for gaining political power within the state. They play a vital role in national development, leading to the establishment of the Political Parties Law to provide a legal framework for their existence. This law also facilitates state financial assistance to political parties, sourced from the National Budget (APBN) and Regional Budget (APBD). With this support comes a responsibility for political parties to submit accurate and transparent reports on how the funds are used. However, instances of misuse and corruption involving these funds are not uncommon. While criminal liability for such corruption typically falls on party officials, the Anti-Corruption Law provides a basis for holding the political parties themselves accountable. This leads to a critical issue of regulatory ambiguity, raising two key questions. First, can political parties be classified as corporations in corruption cases involving state financial assistance? Second, what form of regulation can provide legal certainty regarding the criminal liability of political parties as a corporation in corruption cases involving state financial assistance? Through normative legal research, this study finds that political parties can indeed be classified as corporations under the Anti-Corruption Law, based on both their normative status and identification theory. It also calls for regulatory reforms to establish the criminal liability of political parties. This includes amending the Political Parties Law and related regulations to ensure both political parties and their officials are held accountable in corruption cases involving state financial assistance.